Answer:
f(x) = 2x³ - 10x² - 34x + 42
Explanation:
The standard form of a cubic equation is f(x) = ax³ + bx² + cx + d
Given conditions are:
First: Zeros of the cubic function are - 3, 1, and 7
Second: f(- 2) = 54
a(-3)³ + b(-3)² + c(-3) + d = 0 ⇔ - 27a + 9b - 3c + d = 0 ...... (1)
a + b + c + d = 0 ......... (2)
a(7)³ + b(7)² + c(7) + d = 0 ⇔ 343a + 49b + 7c + d = 0 ....... (3)
a(-2)³ + b(-2)² + c(-2) + d = 54 ⇔ - 8a + 4b - 2c + d = 54 ...... (4)
We have 4 equations with 4 unknown variables.
Use Cramer's rule to solve the system
A =
= 6,480
=
= 12,960
=
= - 64,800
=
= - 220,320
=
= 272,160
a =
= 2
b =
= - 10
c =
= - 34
d =
= 42
f(x) = 2x³ - 10x² - 34x + 42